Stik urbanih površin z gozdom na primeru Krajinskega parka Tivoli, Rožnik in Šišenski hrib - Babič, Tjaša (Gozdarski vestnik, 2024)
In Slovenia, the problematics of the contact of urban areas with the forest have not been entirely discussed, therefore, an example of a study was performed in the eastern part of the Tivoli, Rožnik and Šišenski hrib Landscape Park in Ljubljana, where the conflicts between urban areas and forest ecosystem are frequent. The study included a short overview of the literature, a terrain overview with the recording of the activities on the contact of the urban areas with the forest, and the analysis of the initiatives from the web portal Servis pobude meščanov Ljubljana (Ljubljana Citizens’ initiative service). We recorded the activities with the ArcGIS Survey 123 application. The prevailing improper activities in the studied area included illegal material and waste deposits at the forest edge, followed by uncontrolled spreading of invasive plant species. Forest fires at the forest edge were not among the most striking problems. The citizens highlighted the significance of keeping an orderly and peaceful environment in the landscape park and expressed the importance of good accessibility and traffic regulation. We presented guidelines incorporating preventive measures for decreased fire risk, use of environmentally friendly fences for protection against the game, encouraging planting native non-invasive species, and proper removal of invasive species for effective management of the area on the contact with the urban areas. Making the public aware and cooperating with the local community are key factors for keeping the stability and ecological functionality of the forest edge.
Keywords: conflict contacts; divja odlagališča odpadkov; forest edge; forest fire; gozdni požar; gozdni rob; invasive plants; invazivne rastline; konfliktni stiki; management guidelines; mestni gozdovi; smernice za upravljanje; urban forest; urbani gozdovi; wild waste dumps